2007
DOI: 10.1108/02635570710734280
|View full text |Cite
|
Sign up to set email alerts
|

Key issues and challenges of risk management and insurance in China's construction industry

Abstract: Purpose -The purpose of this study is to investigate the key issues and challenges in risk management and insurance in the Chinese construction industry and propose solutions to improve risk management. Design/methodology/approach -The study is based on surveys which target people who have direct or relevant experience of risk management and construction insurance in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 15 publications
3
54
0
2
Order By: Relevance
“…Liu et al (2007) observed that the ineffective implementations of holistic risk management still exist among Chinese construction firms in Mainland China, and are caused by a lack of formalized risk management procedures, including risk identification, analysis and control; a lack of continuity of risk management in the different stages in the project life cycle, including conceive, design, plan, allocate, execute, deliver, review and support; poor integration between risk management and other key processes, including design, estimating, planning, production, logistics, cost analysis, manufacturing, quality assurance, reliability, schedule analysis, support (e.g. maintainability), and test and evaluation; and a lack of interaction among different parties, including clients, contractors, insurers, and suppliers (Liu et al, 2007).…”
Section: External Risk Managementmentioning
confidence: 97%
“…Liu et al (2007) observed that the ineffective implementations of holistic risk management still exist among Chinese construction firms in Mainland China, and are caused by a lack of formalized risk management procedures, including risk identification, analysis and control; a lack of continuity of risk management in the different stages in the project life cycle, including conceive, design, plan, allocate, execute, deliver, review and support; poor integration between risk management and other key processes, including design, estimating, planning, production, logistics, cost analysis, manufacturing, quality assurance, reliability, schedule analysis, support (e.g. maintainability), and test and evaluation; and a lack of interaction among different parties, including clients, contractors, insurers, and suppliers (Liu et al, 2007).…”
Section: External Risk Managementmentioning
confidence: 97%
“…This method also facilitates the process of retrieving, updating, and exchanging of information. It thus provides useful information in better equipping the construction practitioners to make more informed decisions to the contractual issues in contract administration (Liu et al, 2007). In addition, it also assists contract drafters and experts to review and clarify the clauses of the contract form in a way understandable to the parties.…”
Section: Introductionmentioning
confidence: 99%
“…Material availability Liu et al (2007) Labour productivity Elhag, Boussabaine and Ballal (2005); Shash (1993) Level of profit Park and Chapin (1992) Project financing Han and Diekmann (2001) Cost of manpower Shash (1993) Location and control of site Akintoye (2000) Zonal rates Zou (2007) Category of contractor Shen et al (2004) Management ability Hatush and Skitmore (1999) Contract type Drew and Skitmore (1997) Method of tender selection and degree of competition Oo, Drew and Lo (2008) Government policy Shen et al (2004) Project definition/size Drew and Skitmore (1992) Type of development Fu, Drew and Lo (2003) Construction plan Watt, Kayis and Willey (2009)…”
Section: Factors Referencesmentioning
confidence: 99%